Associations Between Academic Achievement and Psychosocial Variables in Adolescents With Cystic Fibrosis - GRIEVE, ADAM J. (J Sch Health, 2011)
BACKGROUND: Cystic Fibrosis (CF) is a chronic genetic disease that leads to the accumulation of thick mucus in multiple organ systems, leading to chronic lung infection and affecting the body’s ability to absorb nutrients necessary for growth and development. This cross-sectional, correlational study examined the potential effects of CF on students’ psychosocial and academic development. METHODS: Forty adolescents with CF completed a battery of neuropsychological and psychosocial measures. Their school records were reviewed to abstract information about standardized achievement testing results and grade point average (GPA). Academic outcomes were hypothesized to be associated with (a) self-efficacy, (b) disease and school-specific coping strategies, (c) attitude to school, and (e) depression. RESULTS: Cognitive and academic scores were within the normal range, and self-efficacy had the strongest association with standardized cognitive and academic measures and high school grades. School absences were associated with GPA, but not standardized test scores. CONCLUSION: Adolescents with CF require supports in school that foster their sense of self-efficacy and accommodations that address the learning time lost from extended health-related absences.